2004
DOI: 10.1111/j.1048-891x.2004.014204.x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term follow-up of a phase II trial of oral altretamine for consolidation of clinical complete remission in women with stage III epithelial ovarian cancer in the Southwest Oncology Group

Abstract: Consolidation therapy with oral altretamine was generally well tolerated and associated with prolonged progression-free and overall survival in the Phase II setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Despite its tolerability, PLD as a consolidation agent fa i le d to demonst rate a n i mpact on DFS or OS at t he dosage and schedule used in this study. Although the 2-year OS rate of 62% is similar to that previously published for Southwest Oncology Group studies (64%) in suboptimally debulked patients using oral altretamine consolidation therapy [11,12], no difference in survival was noted. The GOG 111 study by McGuire et al [3] also evaluated stage III/IV suboptimally debulked EOC patients treated with cisplatin plus either cyclophosphamide or paclitaxel.…”
Section: Discussionsupporting
confidence: 82%
“…Despite its tolerability, PLD as a consolidation agent fa i le d to demonst rate a n i mpact on DFS or OS at t he dosage and schedule used in this study. Although the 2-year OS rate of 62% is similar to that previously published for Southwest Oncology Group studies (64%) in suboptimally debulked patients using oral altretamine consolidation therapy [11,12], no difference in survival was noted. The GOG 111 study by McGuire et al [3] also evaluated stage III/IV suboptimally debulked EOC patients treated with cisplatin plus either cyclophosphamide or paclitaxel.…”
Section: Discussionsupporting
confidence: 82%
“…Vergote et al reported a 14% response rate of HMM as a single agent in 50 patients with pltinum-resistant disease. And oral altretamine 260 mg/m 2 /day was given for 14 days every 4 weeks for six cycles to patients with FIGO stage III EOC who obtained a clinical response following platinum-based therapy (12). To date, however, there have been no trials comparing HMM with no treatment in patients with advanced EOC.…”
Section: Discussionmentioning
confidence: 99%
“…Consolidation therapy uses one or more of the multiple chemotherapeutic agents known to be active in recurrent disease (5, 6). One of these agents, hexamethylmelamine (HMM), which has been used to treat recurrent ovarian cancer for many years, is well tolerated (7-11) and is associated with prolonged PFS and OS in the Phase II setting (12). Little is known, however, about outcomes of consolidation therapy in advanced EOC patients; and there have been no comparison studies of HMM consolidation therapy in these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Nab-paclitaxel has an overall response rate of 64%. 126 Altretamine has a 14% response rate 127 and ifosfamide a 12% response rate, 128 although less information is available regarding their use in patients who are refractory to paclitaxel. Bevacizumab is also active (21%) in both platinum-sensitive and platinum-resistant patients, [129][130][131][132][133] although it may cause arterial thrombosis or intestinal perforation.…”
Section: Recurrent Diseasementioning
confidence: 99%